Dancing in the rain: selective drivers of variability in Neotropical manakins - Shogren, Elsie Hulda (Kansas State University, 2020)
The overarching goal of this dissertation is to understand how natural and sexual selection interact to drive trait and behavioral evolution. Under challenging abiotic conditions, natural selection is expected to constrain sexual selection, resulting in evolutionary tradeoffs in behavior, morphology, and genetics. In the tropics, precipitation is the main axis of climatic variability, but relatively little is known about the functional relationships between rain and endotherm biology. I focus on how precipitation influences Neotropical birds at multiple levels of biological organization from macroevolutionary patterns across clades to individual behavior within populations. In manakins (Pipridae), a family of sexually-selected Neotropical birds, males perform elaborate courtship displays. Despite consistency of mating system, the direction of sexual size dimorphism (males larger or smaller than females) varies among species. I determined the relative importance of abiotic environmental selection and sexual selection associated with courtship display drove patterns of sexual size dimorphism across 22 species of manakin. Males tended to weigh less than females in species where courtship display involved more aerial elements, suggesting that sexual selection for agility has shaped body size in these species. However, in species found in rainier environments, males had longer wings than females indicating that abiotic constraints also affect morphological evolution in this clade. These types of macroevolutionary patterns are likely shaped by associations between demography and local environmental variation. Consequently, I tested the prediction that inter-annual variation in rainfall influenced estimates of apparent survival using a seven-year capture-mark-recapture dataset for seven Neotropical montane forest bird species. The response to rainfall varied among species; apparent survival decreased following years of heavier rain in three species and increased in two species. Thus, demographic effects of annual precipitation are contingent upon other aspects of species’ ecology and life history. Reduced annual apparent survival may disproportionately limit the strength of sexual selection in long-lived species in which age-graded social hierarchies determine reproductive success. Elevated mortality can reduce reproductive skew by increasing turn-over of dominant individuals resulting in more males gaining opportunities to reproduce. To link abiotic selection to reproductive skew, I sampled White-ruffed Manakins (Corapipo altera) at seven sites varying in precipitation regime. Among populations, reproductive skew, measured by the ratio of nucleotide diversity on the Z chromosome relative to autosomes ranged from 0.53 to 0.56. Reproductive skew was lowest in the populations subject to high and relatively aseasonal rainfall. This suggests that the intensity and timing of precipitation can constrain sexual selection and shape the genetic diversity of a population. Population-specific sources of selection could also influence the stability and scope of male interactions within a population. Male White-ruffed manakins display at sites clustered in “leks.” Individual investment in display behavior is strikingly variable, and males interact frequently on their own and nearby sites. To test whether competition, cooperation, or individual quality drive variation in male behavior, I manipulated the social environment by both increasing acoustic signaling and by temporarily preventing nearby males from displaying. Focal males reduced their investment in vocalization when the acoustic signal was experimentally increased, and females visited focal logs more frequently when nearby logs were covered, but other behaviors remained unchanged. These results are consistent with the hypothesis that males cooperate to advertise display sites, and that likely, condition or quality underlies variation amongst males in other display behaviors. The dissertation as a whole reveals the importance of abiotic, environmental context in studying and interpreting the individual, population-level, and species-level patterns of sexually selected behaviors and morphology in Neotropical birds. By linking ecological abiotic constraints to the evolutionary trajectories of tropical organisms, this dissertation highlights the complex interactions of natural and sexual selection in the evolution of some of the tropics’ most charismatic animals.
Keywords: Behavior; Ecology; Evolution; Precipitation; Sexual selection; Tropical biology